Mga pusang gala (Erasto Films., 2006)
Mga pusang gala tells the story of parallel love stories that of Marta a middle age advertising practitioner, and that of her, just as aging, gay friend and landlord Boyet, a romance novelist. Their lives are punctuated by their waiting for the men who they think will fulfill their dreams. Boyet's novels are inspired by Marta's idiosycratic anxieties for Steve, her-non-committal boyfriend. Marta is tacitly envious of Boyet's gathering of a 'family' by adopting Jojo, a 15-year old pickpocket and Dom, his financially dependent lover. Both are willing to play stereotypical roles of woman and gay to embrace a hopeful fantasy. But as these hopes turn out to be illusions. They decide to take matter into their hands, in a riveting confrontation. What happens next is inevitable but unsettling.